Analysis of Ante Natal Care Services With Satisfaction of Pregnant Women at the Health Center in Kuta Cane City - Martaulina Sinaga (Institute of Computer Science (IOCS), 2021)
Satisfaction with health services provided tends to comply with advice and comply with agreed treatment plans and in carrying out ANC examinations. This study aims to determine the analysis of ANC Services and Satisfaction of Pregnant Women at the Health Center in Kuta Cane City, Southeast Aceh District in 2020. Method: This type of research is observational with a crosssectional approach which aims to explain Ante Natal Care Services with Satisfaction of Pregnant Women. The population in this study were pregnant women who came from 01 January to 31 March 2020 totaling 34 people. The sampling technique takes the entire population of 34 people. The data analysis technique uses the chi square statistical test . Results: This study found that the highest age of pregnant women was 30-35 years, 27 respondents (79.4%), high school education 17 respondents (50%), work as an entrepreneur 15 respondents (44.1%), Parity 2 as many as 14 respondents (41.2%). ANC services for pregnant women in the good category were 30 respondents (88.2%), pregnant women were satisfied with the ante-natal care services in the satisfied category as many as 30 respondents (88.2%), there was a relationship between ante-natal care services and the satisfaction of pregnant women with a value of p = 0.000. The conclusion is that there is a relationship between Ante Natal Care Services and Satisfaction of Pregnant Women at the Kuta Cane City Health Center, Southeast Aceh Regency in 2020. Suggestions to improve ANC services.